Ibn Khaldun - Alatas, Farid, Syed; Oxford Centre for Islamic Studies (New Delhi : Oxford Centre for Islamic Studies ; Oxford University Press, 2013)
On the life and works of Ibn Khaldūn, 1332-1406, Arab Muslim historiographer and historian.
Includes bibliographical references and index.
Keywords: Ibn Khaldūn, -- 1332-1406.; Historians, Arab -- Islamic Empire -- Biography; Science -- Social aspects; Islamic civilization